2018
DOI: 10.1038/s41419-018-0928-8
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal miR-21-5p derived from gastric cancer promotes peritoneal metastasis via mesothelial-to-mesenchymal transition

Abstract: Peritoneal metastasis is a primary metastatic route for gastric cancers, and the mechanisms underlying this process are still unclear. Peritoneal mesothelial cells (PMCs) undergo mesothelial-to-mesenchymal transition (MMT) to provide a favorable environment for metastatic cancer cells. In this study, we investigated how the exosomal miR-21-5p induces MMT and promotes peritoneal metastasis. Gastric cancer (GC)-derived exosomes were identified by transmission electron microscopy and western blot analysis, then t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
135
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 166 publications
(136 citation statements)
references
References 47 publications
1
135
0
Order By: Relevance
“…It is reported that miRNA is involved in tumorigenesis, acting variously as either oncogenes [24][25][26][27] or tumor suppressors. 16,28,29 Increasing evidence has demonstrated that miRNAs are effective biomarkers and tumor regulators in kidney cancer and therefore have broad implications in both clinical and therapeutic practice.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that miRNA is involved in tumorigenesis, acting variously as either oncogenes [24][25][26][27] or tumor suppressors. 16,28,29 Increasing evidence has demonstrated that miRNAs are effective biomarkers and tumor regulators in kidney cancer and therefore have broad implications in both clinical and therapeutic practice.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that mesothelial cells showed increased vimentin and αSMA expressions and decreased E‐cadherin expression during the MMT process . Therefore, immunoreactivity of a human mesothelial cell line (Met‐5A) separately cocultured with NIH3T3‐miR‐21‐mimic (Figure A) was studied.…”
Section: Resultsmentioning
confidence: 49%
“…In peritoneal dissemination, the MMT is important in the cancer microenvironment . To assess whether the MMT is also observed in the cancer microenvironment in pleural dissemination, surgically resected pleural disseminated nodules of lung adenocarcinomas were studied (Figure A‐C) by double‐staining immunohistochemistry using calretinin, desmin, and αSMA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations